Distributed emergency control method for integrated energy system in industrial park based on alternating direction multiplier method - Li, Wenbin; Jia, Lijing; Xu, Baoyu; Lu, Rongfei; Huang, Yu (Frontiers in Energy Research, 2025)
With the rapid development of integrated energy systems (IES), the extensive integration of dis-tributed energy and the increasing coupling of multiple energy systems need higher requirements for the coordinated control methods of IESs. This paper proposes a distributed emergency control method for integrated energy systems of industrial parks based on the alternating direction multiplier method (ADMM). Firstly, an optimization scheduling model is established for the integrated energy system in industrial parks. On the basis of minimizing operating costs, the model takes into account the operational constraints of each energy equipment. Secondly, considering the shortage of energy supply, in order to achieve energy transfer between users, a distributed optimization scheduling model for IES of the industrial park is established based on the typical energy structure of users. And a distributed optimization scheduling algorithm for the comprehensive energy system of the industrial park based on ADMM is proposed. Finally, the proposed emergency control method is verified under typical fault scenarios.